2020
DOI: 10.1111/irv.12783
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 environmental contamination associated with persistently infected COVID‐19 patients

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
83
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 17 publications
6
83
0
1
Order By: Relevance
“…- [208] cps = copies per swab; cpm = copies per ml; *proportion of room with at least one environmental surface contaminated; **door handles; ***after cleaning and disinfection; ****detection of infectious SARS-CoV-2 was attempted in all samples and was consistently negative; *****only on ventilator tubing before HME filter.…”
mentioning
confidence: 99%
“…- [208] cps = copies per swab; cpm = copies per ml; *proportion of room with at least one environmental surface contaminated; **door handles; ***after cleaning and disinfection; ****detection of infectious SARS-CoV-2 was attempted in all samples and was consistently negative; *****only on ventilator tubing before HME filter.…”
mentioning
confidence: 99%
“…After further screening, and supplementary searching of articles published or posted between 1 January 2020 and 21 July 2020, we identified an additional article and a total of 17 articles were included in the review (Figure 1). [3,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]…”
Section: Search Resultsmentioning
confidence: 99%
“…When using sing a human adenovirus virus (HAdV), Verani et al, 52 found 135 out of 172 surfaces within toilet facilities in a health care setting to be contaminated. Contamination of contact surfaces outside the sanitation setting has been reported in hospitals 55,56,57,58 home settings 59,60,61 and public spaces 60 .…”
Section: Discussionmentioning
confidence: 99%